Jalinan Institusi Pendidikan Tinggi Islam di Malaysia dan Indonesia - Rahimin Affandi Abdul Rahim, Abdul Halim Mat Diah Moh. Faisol Abdul Hamid (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
Abstract: In academic world there is an axiom which declares that every science discovered by human being through scientific research should be based on solid theoretical framework which will be used as a way of thinking paradigm or solving problem philosophy. This paradigm should be in dynamic condition and used to solve problematic issues. revewing process to clarify the truth of the theory is applicable to all knowledge, such as religion, pure and social science. In order to develop link between Indonesia and Malaysia educational institution, an altemative paradigm framewrok is needed to be put into action. This alternative paradigm is a necessity to discuss the history of the development of Islam in Malay region which is suited with lslamic worldview as well as the unique and specific nature of Malay.